Risk of Elevated Blood Glucose Levels in Tuberculosis Patients with BTA 3+ Levels, Puskesmas Bojong Gede Kabupaten Bogor - Febrial Hikmah (Jurnal Analis Medika Biosains (JAMBS), 2020)
Tuberculosis (TB) is a contagious infectious disease caused by the bacterium Mycobacterium tuberculosis. TB cases are still high that has attracted many researchers to conduct studies, especially the factors that cause therapy failure. TB patients who undergo therapy will be at risk of experiencing changes in carbohydrate metabolism. This is compounded by the condition of patients who have a history of diabetes mellitus (DM) before. Therefore, examination of blood glucose in TB patients is considered necessary to be a series in therapy. The increased risk was also influenced by several factors, including age and gender. The data was taken cross sectional as many as 57 samples of TB patients with various AFB positivity levels. The results obtained that 75% of TB patients included in the positive category 3 AFB, 46% aged >40 years, and 61% were male. Mean blood glucose level of 165 ± 14 mg/dL. About 19% of patients have glucose levels >200 mg/dL. Of the 19% of these patients 91% of patients were in the BTA positive category 3, 91% were aged >40 years and 73% were male. The conclusion is that there is a risk of an increase in blood glucose levels in TB patients with level 3+ AFB.